ANALYSIS OF IMPROVING TEACHER PERFORMANCE AND WORK ENVIRONMENT AND PROFESSIONALISM - Nirwana, Ida; Amelia, Indri; Yeni, Afni; Putra, Ramadhani Kirana (Manager : Jurnal Ilmu Manajemen, 2024)
This research aims to see the influence of the work environment and professionalism on teacher performance at SMP N 3 Gunung Talang, Solok Regency. The type of research used is descriptive correlative research. Correlative descriptive is a research method that aims to see the relationship between two or more variables. The variable that influences is the independent variable (X), while the variable that is affected by the independent variable is called the dependent variable (Y). Based on the research results, the multiple linear regression equation is Y = 17.868 -0.063X1 +0.603X2 +e The constant value is 17.868. The research results determined the determination value with an Rsquare of 0.605 or 60.5%. H1 is accepted with a tcount value of -0.554 < ttable 2.051 and a significance value greater than α 0.05 (0.584 > 0.05), H2 is accepted with a tcount value of 6.394 < ttable 2.051 and a significance value smaller than α 0.05 ( 0.000 > 0.05). H3 does not have a significant and simultaneous influence on teacher performance with an Fcount value of 20.642 < Ftable 3.34 and a significance value of 0.000 > 0.05.